2023
DOI: 10.1021/acsinfecdis.3c00010
|View full text |Cite
|
Sign up to set email alerts
|

hACE2-Induced Allosteric Activation in SARS-CoV versus SARS-CoV-2 Spike Assemblies Revealed by Structural Dynamics

Abstract: SARS-CoV and SARS-CoV-2 cell entry begins when spike glycoprotein (S) docks with the human ACE2 (hACE2) receptor. While the two coronaviruses share a common receptor and architecture of S, they exhibit differences in interactions with hACE2 as well as differences in proteolytic processing of S that trigger the fusion machine. Understanding how those differences impact S activation is key to understand its function and viral pathogenesis. Here, we investigate hACE2-induced activation in SARS-CoV and SARS-CoV-2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 49 publications
1
21
0
Order By: Relevance
“…The recent HDX-MS studies of ACE2-induced allosteric activation of the S protein demonstrated allosteric changes upon ACE2 binding that extend to the hinge region and the top of the central helical bundle of the S2 subunit [38]. The experiments showed that ACE2 binding allosterically perturbs and primes HR1 and regions flanking the S1/S2 cleavage site for cleavage [3638].…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The recent HDX-MS studies of ACE2-induced allosteric activation of the S protein demonstrated allosteric changes upon ACE2 binding that extend to the hinge region and the top of the central helical bundle of the S2 subunit [38]. The experiments showed that ACE2 binding allosterically perturbs and primes HR1 and regions flanking the S1/S2 cleavage site for cleavage [3638].…”
Section: Resultsmentioning
confidence: 99%
“…The recent HDX-MS studies of ACE2-induced allosteric activation of the S protein demonstrated allosteric changes upon ACE2 binding that extend to the hinge region and the top of the central helical bundle of the S2 subunit [38].…”
Section: Mediating Network Of Conserved Allosteric Sitesmentioning
confidence: 99%
See 3 more Smart Citations